1982
DOI: 10.1172/jci110647
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism of Human Neutrophils during Phagocytosis

Abstract: A B S T R A C T Detailed quantitative studies were performed on the generation and utilization of energy by resting and phagocytosing human neutrophils. The ATP content was 1.9 fmol/cell, was constant during rest, and was not influenced by the presence or absence of glucose in the medium. The intracellular content of phosphocreatine was less than 0.2 fmol/cell.In the presence of glucose, ATP was generated almost exclusively from lactate produced from glucose taken up from the surrounding medium. The amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
379
1
5

Year Published

1984
1984
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(408 citation statements)
references
References 30 publications
23
379
1
5
Order By: Relevance
“…On the basis of cell volume, this number is close to the values found in human neutrophils [24] and human lymphocytes [25], but is about 2.5-fold higher than in rabbit reticulocytes [26] and even more than 150-times higher than in rabbit [26] and human [27] erythrocytes. Compared to other cells, therefore, platelets have a high ATP turnover, which is the more puzzling since platelets lack a number of energy-consuming processes that are common in many other cells, such as protein synthesis, biosynthesis of complex carbohydrates, etc.…”
Section: Discussionsupporting
confidence: 80%
“…On the basis of cell volume, this number is close to the values found in human neutrophils [24] and human lymphocytes [25], but is about 2.5-fold higher than in rabbit reticulocytes [26] and even more than 150-times higher than in rabbit [26] and human [27] erythrocytes. Compared to other cells, therefore, platelets have a high ATP turnover, which is the more puzzling since platelets lack a number of energy-consuming processes that are common in many other cells, such as protein synthesis, biosynthesis of complex carbohydrates, etc.…”
Section: Discussionsupporting
confidence: 80%
“…This can be explained by the fact that neutrophils mainly use glycolysis rather than mitochondrial oxidative phosphorylation for their energy supply. 2 Accordingly, inhibitors of glycolysis such as sodium iodoacetate and 2-deoxyglucose caused a profound ATP loss with less than 1% of ATP remaining in comparison to untreated neutrophils ( Figure 1; and data not shown). Moreover, two important mitochondrial enzymes, glutamate dehydrogenase (GDH) and fumarase, which are often used as markers of mitochondria, 10-12 displayed a borderline low activity in neutrophils in contrast to HL-60 cells, which have actively respiring mitochondria 13,14 (Figure 2).…”
Section: Resultsmentioning
confidence: 88%
“…This point of view was mainly based on the observation that mitochondrial poisons like cyanides do not influence cellular functions in neutrophils. 2 Moreover, electron microscopy studies identified hardly any mitochondria in neutrophils (see the references in Fossati et al 3 ), and mitochondrial respiration was found to be very low in these cells. 4 However, mitochondria have been recently visualized in neutrophils as a tubular network, by means of specific fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%
“…high 5 0 -AMP levels), could contribute to save ATP. Early reports on phagocytic cells have reported an enhanced requirement of energy when these become activated during phagocytosis, or by treatment with PMA and lipopolysaccharides [23]. It is known that endogenous levels of ATP are depleted during phagocytosis [23,25], and hence the requirement of extra energy to provide NADPH as a substrate for the oxidase reaction during phagocytosis could be provided by an enhancement of glycogen degradation and glucose oxidation through glycolysis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Early reports on phagocytic cells have reported an enhanced requirement of energy when these become activated during phagocytosis, or by treatment with PMA and lipopolysaccharides [23]. It is known that endogenous levels of ATP are depleted during phagocytosis [23,25], and hence the requirement of extra energy to provide NADPH as a substrate for the oxidase reaction during phagocytosis could be provided by an enhancement of glycogen degradation and glucose oxidation through glycolysis [23]. We have reported that activated peritoneal macrophages from Escherichia coli-treated rats showed an enhanced glycolytic rate, as measured on the basis of fructose 2,6-bisphosphate levels, a stimulator of this metabolic pathway, as well as by lactate production [45].…”
Section: Discussionmentioning
confidence: 99%